STUDYING THE STAGES OF THE HISTORICAL DEVELOPMENT OF THE LANDSCAPE GENRE AND ITS IMPORTANCE IN THE DEVELOPMENT OF THE ARTISTIC AND CREATIVE SKILLS OF FUTURE VISUAL ARTS TEACHERS - Abdimuminov Muhammad Sadiq (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2024)
The teaching methodology of painting in the landscape genre. The history of the emergence, development and formation of the landscape genre in painting is directly related to the development of the landscape as a visual art genre. Many generations of artists have given their talent to it. The influence of nature on a person, the deep feelings and thoughts it causes, which led to the emergence of this genre in visual art, is given.